2010
DOI: 10.1016/j.jcv.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human coronaviruses in children with acute gastroenteritis

Abstract: This study shows that all known non-SARS HCoVs can be found in stools of children with acute gastroenteritis. On the basis of this study, the significance of coronaviruses as gastrointestinal pathogens in children appears minor, since most of the coronavirus findings were co-infections with known gastroenteritis viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 36 publications
8
61
1
4
Order By: Relevance
“…Over the years, the four circulating HCoV have been associated with pathologies outside the respiratory tract, such as myocardites and meningitis (Riski and Hovi, 1980) and severe diarrhea (Gerna et al, 1985;Resta et al, 1985), as seen with animal coronaviruses. Recent investigations on the HCoV as enteric pathogens demonstrated that all the HCoV can be found in stool samples of children with acute gastroenteritis but could not conclude on their "true association" with disease etiology (Esper et al, 2010;Risku et al, 2010). As previously mentioned, different reports have also presented a possible link between the presence of HCoV within the human central nervous system (CNS) and some neurological disorders (Arbour et al, 2000;Cristallo et al, 1997;Fazzini et al, 1992;Stewart et al, 1992;Yeh et al, 2004).…”
Section: Human Coronaviruses: Recognized Respiratory Pathogensmentioning
confidence: 99%
“…Over the years, the four circulating HCoV have been associated with pathologies outside the respiratory tract, such as myocardites and meningitis (Riski and Hovi, 1980) and severe diarrhea (Gerna et al, 1985;Resta et al, 1985), as seen with animal coronaviruses. Recent investigations on the HCoV as enteric pathogens demonstrated that all the HCoV can be found in stool samples of children with acute gastroenteritis but could not conclude on their "true association" with disease etiology (Esper et al, 2010;Risku et al, 2010). As previously mentioned, different reports have also presented a possible link between the presence of HCoV within the human central nervous system (CNS) and some neurological disorders (Arbour et al, 2000;Cristallo et al, 1997;Fazzini et al, 1992;Stewart et al, 1992;Yeh et al, 2004).…”
Section: Human Coronaviruses: Recognized Respiratory Pathogensmentioning
confidence: 99%
“…MERS-CoV emerged in Saudi Arabia in 2012, and at the time of this writing, has resulted in 1110 confirmed cases and 456 deaths. The remaining three human coronaviruses (HCoVNL63, HCoV-OC43, and HCoV-229E), have been detected in stool samples 25,67,68 but are not believed to play a significant role in infections of the gastrointestinal tract. 65 Likewise, human coronavirus HKU1 (HKU1-CoV) RNA has also been detected in stool samples, 66 in some cases from patients exhibiting gastrointestinal symptoms.…”
Section: Avian Influenza Virusesmentioning
confidence: 99%
“…[120][121][122] Degenerate primers are also used to detect a range of coronaviruses. 68,123,124 Due to their varied cell tropisms, human coronaviruses cannot be cultured in the same type of cell systems. 68,123,124 Due to their varied cell tropisms, human coronaviruses cannot be cultured in the same type of cell systems.…”
Section: Detecting Enveloped Viruses In Watermentioning
confidence: 99%
“…3). As in the case of SARS and other coronaviruses, feces, 66,94 urine, 64,66 and sera 95 might be useful and should be collected for further testing as clinically indicated.…”
Section: Laboratory Diagnosis and Gene Targetsmentioning
confidence: 99%